2014
DOI: 10.1016/j.jaac.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Mood Dysregulation Disorder and Chronic Irritability in Youth at Familial Risk for Bipolar Disorder

Abstract: Objective Disruptive mood dysregulation disorder (DMDD) is a new diagnosis in the DSM-5. Youth with a family history of BD are at increased risk for BD and non-bipolar psychopathology. No studies to date have examined rates of DMDD among offspring of parents with BD. This study examines the risk for DMDD in offspring of parents with BD compared to community controls and considers rates of chronic irritability (independent of a DMDD diagnosis) across diagnoses in youth with parents with BD. Method Modified DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
3
35
3
4
Order By: Relevance
“…It was associated with poorer functioning across multiple domains but many relationships attenuated when adjusting for common comorbidities; however, DMDD was independently associated with some aspects of poorer social functioning and poorer family quality of life even when comorbidities were taken into account. Similar to a number of previous studies [7,[9][10][11], we found a very high co-occurrence between ODD and DMDD (90 %) in this sample of children with ADHD. These findings have raised questions about whether ODD and DMDD are truly independent.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was associated with poorer functioning across multiple domains but many relationships attenuated when adjusting for common comorbidities; however, DMDD was independently associated with some aspects of poorer social functioning and poorer family quality of life even when comorbidities were taken into account. Similar to a number of previous studies [7,[9][10][11], we found a very high co-occurrence between ODD and DMDD (90 %) in this sample of children with ADHD. These findings have raised questions about whether ODD and DMDD are truly independent.…”
Section: Discussionsupporting
confidence: 91%
“…However, research to date has generally disregarded this rule in order to examine the diagnostic overlap between these conditions. ODD is the most common comorbidity in children with DMDD with 57-96 % also meeting criteria for ODD [7,[9][10][11], raising questions about the validity of DMDD as a separate diagnostic category. While most children with DMDD meet criteria for ODD, only 20-40 % of children with ODD meet criteria for DMDD [7].…”
Section: Disruptive Mood Dysregulation Disorder: Definition Prevalenmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on retrospective studies of both adults and children, sleep disturbances, anxiety, depressive symptoms, affective lability, subthreshold hypomanic symptoms, behavioral dyscontrol, and irritability have been reported to precede bipolar disorder (3,79). Many of these characteristics have also been identified in youth at genetic risk for bipolar disorder (1018). …”
mentioning
confidence: 99%
“…In fact, as Vidal-Ribas et al note, heritability of irritability overlaps with depression, and there is a significant relation between maternal depression and offspring irritability. Moreover, significantly more offspring of parents with bipolar disorder (BD) had a proxy diagnosis of DMDD than offspring of controls, 12 and DMDD offspring of parents with BD were at higher risk of developing BD than those without DMDD (Axelson et al, unpublished data).…”
mentioning
confidence: 99%